Advances in computational dynamics of particles, materials and structures a unified approach - Har, Jason (Wiley, 2012)
Advanced Computational Dynamicsof Particles, Materials, and Structures: A Unified Approach breaks new ground with its in-depth, detailed coverage of modern computational mechanics in particle and continuum dynamics. Kumar Tamma provides a unique blend of classical and innovative theoretical and computational approaches that cover both particle dynamics and flexible continuum structural dynamics applications. He covers both traditional methods and new developments & perspectives in both time and space discretization, encompassing classical Newtonian, Lagrangian, and Hamiltonian mechanics as well as new and alternate contemporary approaches and their equivalences to address various problems in engineering sciences and physics. The completeness and depth of coverage makes Advanced Computational Dynamics of Particles, Materials, and Structures an invaluable reference for both engineers and researchers working in the field of computational mechanics.